DECISION MAKING CHALLENGES IN ACUTE STROKE - Sajjad, Muhammad Mohsin; Corrigan, John; Anjum, Muhammad Sajjad (Pakistan Armed Forces Medical Journal, 2020)
A 72 years old gentleman with no significant past medical history presented to our hospital with acute onset Right Ischemic arm, a CT with contrast of arm showed right brachial clot. Heparin 5000iu bolus was given, infusion was commenced and arrangements for transfer to specialized vascular team was made, during transfer patient developed left-sided weakness and slurring of speech. As per protocol patient was returned back to nearest hospital. An urgent CT Brain was done (D-CTB 5min) as per guidelines for FAST positive or stroke patients (fig-1). Baseline investigations showed creatinine of 124. We had the Clinical Challenges like, can we repeat CT Angiogram considering elevated creatinine levels and the risks of thrombolysis following IV Heparin as the patient was within the thrombolytic window (4.5 hrs).